2 GOSH speaks up. (22nd November 2019) - Long, Andrew; Panesar, Karen; Leonard, Amy; Knott, Craig
Abstract : Great Ormond Street Hospital encourages all staff to 'Speak Up' to aid in the early identification of patient safety concerns and prevent unintended harm. We believe that training all our staff and volunteers to feel confident, empowered and supported will enable them speak up in the moment. To ensure the safest care for patients we support staff to speak up immediately if they have any concerns about patient safety, rather than relying on reporting after the event that caused concern. This is a skill that GOSH is working to embed in our culture and to do this all staff and volunteers within GOSH will receive training to develop skills and insights to respectfully raise issues with colleagues when they are concerned. We know that supporting our staff to speak up without fear of adverse outcome creates a happier and more fulfilled workforce. In partnership with other hospitals worldwide, through the Medical Protection Society and the Cognitive Institute, we have committed to train all staff at GOSH to use a tool (The Safety Code) to express their concerns without fear of embarrassment or retribution. Experience from our partners has already shown that use of the tool has had a direct impact on patient safety. Within our own experience, with over 50% staff trained we have already seen staff feeling safer to speak up and examples of avoidable errors mitigated. The next phase of this ambitious programme, due to launch shortly, is 'Speak Up for our Values'. This graduated intervention model will address behaviours that undermine a culture of safety and quality. This stage of the programme will encourage the use of 'compassionate conversations' where concerns have been raised about behaviours that do not match GOSH values to help support a culture of kindness and a more positive response to speaking up.